2016
DOI: 10.3847/1538-4357/833/1/93
|View full text |Cite
|
Sign up to set email alerts
|

Return of the King: Time-Series Photometry of Fo Aquarii’s Initial Recovery From Its Unprecedented 2016 Low State

Abstract: Publication date 2016-12-09Original citation Colin, L. et al (2016) ABSTRACT In 2016 May, the intermediate polar FOAqr was detected in a low state for the first time in its observational history. We report time-resolved photometry of the system during its initial recovery from this faint state. Our data, which includes high-speed photometry with cadences of just 2 s, show the existence of very strong periodicities at 22.5 and 11.26 minutes, equivalent to the spin-orbit beat frequency and twice its value, re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…In the case of discless accretion, the power spectrum should be dominated by the beat frequency ω − Ω between the spin and orbital frequency and its first harmonic 2ω − 2Ω, whereas in the case of disc accretion, the spin frequency should be dominant (Ferrario & Wickramasinghe 1999). Littlefield et al (2016) found that, in the low state, the beat component amplitude is more than twice that of the spin component, while in the hight state, it is only 20% of the spin component. Although the modelling of the power spectrum is complex due to the complex geometry of the accretion flow and to the contribution of several sources to the optical light (see above), the change in the power spectrum clearly supports our finding that the disc disappears during the low state.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In the case of discless accretion, the power spectrum should be dominated by the beat frequency ω − Ω between the spin and orbital frequency and its first harmonic 2ω − 2Ω, whereas in the case of disc accretion, the spin frequency should be dominant (Ferrario & Wickramasinghe 1999). Littlefield et al (2016) found that, in the low state, the beat component amplitude is more than twice that of the spin component, while in the hight state, it is only 20% of the spin component. Although the modelling of the power spectrum is complex due to the complex geometry of the accretion flow and to the contribution of several sources to the optical light (see above), the change in the power spectrum clearly supports our finding that the disc disappears during the low state.…”
Section: Discussionmentioning
confidence: 97%
“…It is interesting to note that the partial eclipse shape changed during the low state; the eclipses became narrower and less deep, indicating that the accretion disc had shrunk (Littlefield et al 2016). As the phased light curve over the orbital period was calculated by Littlefield et al (2016) over their entire dataset, it is not possible to decide from these observations if the accretion disc completely disappeared at some point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FO Aqr is an intermediate polar that has never shown outbursts, and can therefore be considered as steady, but was observed to enter a low state in 2016 (more than 2 mag decrease), from which it gradually recovered between May and July 2016 (Littlefield et al 2016). The partial eclipse observed during the low state is narrower and shallower than in the high state, indicating that an accretion disc is still present, albeit smaller than during the high state.…”
Section: The Case Of Fo Aqrmentioning
confidence: 98%